Properties of microcrystalline cellulose extracted from soybean hulls by reactive extrusion. (July 2015) - Merci, Aline; Urbano, Alexandre; Grossmann, Maria Victória E.; Tischer, Cesar A.; Mali, Suzana
Abstract: The objectives of this study were to produce microcrystalline cellulose (MCC) from soybean hulls (SH) employing a simple method based on reactive extrusion, and to characterize the product according its microstructure, morphology, crystallinity and thermal stability. MCC was obtained from SH after a two-step extrusion process; in the first step, the SH was extruded with sodium hydroxide (NaOH), followed by extrusion with sulfuric acid (H2 SO4 ) in the second step. The MCC produced from SH by reactive extrusion was composed of short and rod shaped fibers, with a cellulose content of 83.79% and a crystallinity index of 70%. Reactive extrusion is an alternative and effective method for the production of MCC from lignocellulosic residues, and has the advantages of simplicity and was less polluting than conventional methods. Highlights: Microcrystalline cellulose was obtained from soybean hulls by reactive extrusion. Extrusion process was carried out in two steps, first with NaOH, followed by H2 SO4 . Reactive extrusion was effective in obtaining MCC with less effluent production. MCC from soybean hulls were 83.79% cellulose and 70% crystallinity.